Perancangan Sistem Informasi Pembayaran SPP Berbasis Web Di SMP Islam Parung Dengan Metode Waterfall - Dafa Ramadhan, Aditya; Abiyyu Ghanim, Namero; Dzulkifli Hidayah, Muh.; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
This research aims to design a web-based information system for managing tuition fee payments (SPP - Sumbangan Pembinaan Pendidikan) at SMP Islam Parung. The system is developed using the Waterfall method, consisting of requirement analysis, system design, implementation, testing, and maintenance phases. Requirement analysis is conducted by collecting data through observation, interviews, and literature studies. System design includes database design, user interface design, and business process flow design. Implementation is carried out using PHP programming language and MySQL database. System testing is performed using black-box testing  to ensure functionality and conformance with user requirements. The result of this research is a web-based tuition fee payment information system that can facilitate the payment process, recording, and reporting efficiently and in a computerized manner. This system is expected to improve performance and transparency in the management of tuition fee payments at SMP Islam Parung.